KETERAMPILAN APA YANG SIAP DIGUNAKAN GEN Z SAAT BEKERJA DI ERA INDUSTRI 4.0: BUKTI DI PENDIDIKAN TINGGI INDONESIA - Fery Riyanto; Hardani Widhiastuti; Rusmalia Dewi (Journal of Applied Management Studies, 2023)
Universities around the world have recently expanded their attention to include “employability skills,” which are the soft and hard skills deemed relevant and important for graduates to start a career in a rapidly changing labor market. This research looks at competency, hard skills, and soft skills, as well as work preparation in the industrial era 4.0 among Indonesian state and private university students in Generation Z. Work preparation in the industrial era 4.0, competency, hard skills and soft skills are the variables used. in this research. All participants in this research were students from Indonesian public and private universities, or generation Z. A total of 400 final semester Generation Z students aged 18 to 28 years were used as samples in this research. Proportional random sampling is the method used for sampling. Questionnaires are used in survey data collection methods. AMOS 26 software was used in the data analysis procedure for this research with the Structural Equation Model (SEM). The findings of this research indicate that although soft skills have a direct or indirect impact on job readiness, hard skills have an indirect effect.